Active control of a robotic arm with pneumatic artificial muscle actuator - Hossein Jahanabadi, 1980-, author; Musa Mailah, 1963-, author; Mohd. Zarhamdy Md. Zain, author; South East Asian Technical University Consortium (SEATUC) Symposium (3rd : 2009 : Johor) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL